A comparative study between total laparoscopic hysterectomy and total abdominal hysterectomy for benign uterine conditions - Shakuntla; Nagar, Oby (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The aim of this prospective study is to evaluate and compare the results of two routes of hysterectomy for benign uterine conditions of less than 14 weeks who performed in our tertiary centre. Methods: This was a prospective interventional single centre study on 140 consecutive patients (70 patients in each group) who underwent hysterectomy for benign uterine conditions either by total laparoscopic hysterectomy (TLH) or by total abdominal hysterectomy (TAH) route. Results: There were no statistical differences between two groups regarding age, parity, previous history of abdominal surgery, demographic factors, For TLH group vs. TAH group- operative time was (89.34±12.3 minutes) vs. (46.6±5.92 minutes) (p<0.0001), blood loss (19.61±2.34 ml) vs. (124.8±17.29 ml) (p<0.0001), post operative haemoglobin drop (0.34±0.15 gm/dl) vs. (1.36±0.24 gm/dl) (p<0.0001), pain score (2.56±0.97) vs. (5.31±1.02) (p<0.0001), mean ambulation time (15.16 ± 4.64 hours) vs. (48.76±5.08 hours) (p<0.0001), mean time to catheter removal (12.47±0.94 hours) vs. (48.23±0.64 hours) (p<0.0001), hospital stay (3.74±0.50 days) vs. (7.64±0.98 days) (p<0.0001), resumption to normal daily activities (4.39±0.2 weeks) vs. (11.8±1.77 weeks) (p<0.0001), were significantly lower and earlier in TLH group as compared to TAH group, also compared intra-operative and post-op complication (less in TLH group) and patient satisfaction score(better in TLH group). Conclusions: TLH route is safe and feasible as compare to TAH route and found to have, less amount of blood loss, fewer complications and early ambulation, recovery and discharge.